Clinical perspectives and therapeutic strategies: pediatric autoinflammatory disease-a multi-faceted approach to fever of unknown origin of childhood - Akihiro Yachie (BMC, 2022)
Abstract Among the different etiologies for fever of unknown origin in children, infectious diseases are the most frequent final diagnosis, followed by autoimmune diseases and malignancies. Autoinflammatory diseases are relatively rare among children and are frequently overlooked as differential diagnoses for fever of unknown origin. Once the possibility of a particular autoimmune disease is considered by physicians, the diagnosis might be easily made by a genetic approach because many of autoinflammatory diseases are of monogenic origin. To reach the diagnosis, detailed history-taking, precise physical examinations, and cytokine profiling as well as extensive mutation analysis of candidate genes should be undertaken for febrile children. Such the approach will protect the patients, and their family to undergo "diagnostic odyssey" in which unnecessary and sometimes risky diagnostic and therapeutic interventions are taken. This short review discusses the clinical and laboratory features of familial Mediterranean fever and systemic juvenile idiopathic arthritis, as representative illnesses of monogenic and polygenic autoinflammatory diseases, respectively. Cytokine profiling and mutation analyses both help to understand and decipher the heterogeneous pathologies in both disease categories.